Deformation of an Encapsulated Leukemia HL60 Cell through Sudden Contractions of a Microfluidic Channel - Mohammad Nooranidoost; Ranganathan Kumar (Micromachines, 2021)
Migration of an encapsulated leukemia HL60 cell through sudden contractions in a capillary tube is investigated. An HL60 cell is initially encapsulated in a viscoelastic shell fluid. As the cell-laden droplet moves through the sudden contraction, shear stresses are experienced around the cell. These stresses along with the interfacial force and geometrical effects cause mechanical deformation which may result in cell death. A parametric study is done to investigate the effects of shell fluid relaxation time, encapsulating droplet size and contraction geometries on cell mechanical deformation. It is found that a large encapsulating droplet with a high relaxation time will undergo low cell mechanical deformation. In addition, the deformation is enhanced for capillary tubes with narrow and long contraction. This study can be useful to characterize cell deformation in constricted microcapillaries and to improve cell viability in bio-microfluidics.